Protocolo de medición de elementos radioactivos en los cortes de perforación de yacimientos no convencionales. (2022)
The objective of this monograph is to carry out a protocol for measuring radioactive elements, present in the drilling cuts that originate from the multistage hydraulic fracturing technique with horizontal drilling - FH-PH, establishing parameters, sampling measures and monitoring for the determination of radioactive elements from natural sources. It seeks to establish different criteria related to sampling techniques, the use of materials and tools, equipment, the delimitation of the sampling area, performance criteria, as well as the requirements for their management and conservation, in this way to study the potential emission of radionuclides during the hydraulic fracturing process and if any type of dispersion of radioactive materials related to this activity occurs.